Challenges of COVID-19 prevention during protracted conflicts: differential adherence to preventive measures in “contact line” regions in eastern Ukraine - Cha, Jiho; Noh, Jin-Won; Robinson, Courtland; Kwon, Young Dae; Kim, Jinseok (Frontiers in Public Health, 2023)
Objectives Despite the epidemiological importance of social vulnerabilities in compliance with preventive measures, little is known about the disproportional nature of preventive behaviors in crisis-affected populations. We examined adherence to COVID-19 preventive behaviors, focusing on social distancing measures in the conflict-affected regions in eastern Ukraine. Methods From a multisectoral needs assessment conducted in 2020 using a household interview of a stratified simple random sample, we included 1,617 rural and urban households located in the government-controlled area. We performed multivariable binary logistic regression analysis with latent class analysis (LCA) to identify unmeasured patterns of classification of preventive measures using data from a cross-sectional survey. Results The conflict-affected populations showed difficulty in complying with COVID-19 preventive measures due to losses of housing, partners, and access to food resources due to conflicts. Among the various preventive measures, wearing a face mask (88.1%) and washing hands more regularly (71.4%) were the most frequently reported. Compliance with social distancing was significantly lower in those who experienced the direct impacts of conflicts indicated by damaged accommodation or being widowed. Three different groups who showed distinctive patterns of employing COVID-19 preventive measures were identified via the LCA model, which were “highly complying group”, “moderately complying group”, and “face masks only group”. The group membership was associated with a respondent’s poverty status. Conclusion The findings show the difficulty in compliance with COVID-19 preventive measures among conflict-affected populations indicating secondary impacts of the conflicts on preventive health behaviors. To mitigate the health impacts of conflicts, immediate attention is needed to address barriers to COVID-19 preventive measures among conflict-affected populations in Ukraine. This study suggests the need for public health strategies to improve preventive health behaviors in conflict-affected populations under pandemics or large-scale outbreaks.